Adaptive Heterogeneous Network Handoff of Smartphone Based on the Closed Control Loop - Wei Liu; Qiang Li; Yongle Chen; Yongping Xiong; Yubo Deng; Limin Sun (International Journal of Distributed Sensor Networks)
Owing to complementary characteristics of wireless networks, it is deserved to achieve automatic handoff on the modern smartphone for taking full exploitation of these accessible technologies. In this paper, we have proposed the closed loop model on smartphone switching heterogeneous wireless networks, which is full-client based without requiring additional support from the access points or gateways and modification of the network protocols. It only intuitively takes advantage of user scheme as the feedback adjustment approach to handoff policy. Furthermore, we have analyzed the closed loop handoff model to illustrate and evaluate how the user feedback of the policy acts on adapting to change context. In the experiment, we have evaluated four metrics on the closed loop handoff policy in real smartphone device: performance, energy saving, data offloading, and user experience.